Performance â€œEllen with Will Smith Full Interviewâ€ Talk Show: Emotive Language Functions - Yusuf, Faidah (Jurnal Ilmiah Bina Bahasa, 2020)
This study is focused to analyze the emotive language functions in the Ellen DeGeneres talk show. The objective of this study is to describe the emotive language functions work in the conversation performance by the actors â€œEllen with Will Smith Full Interviewâ€ talk show. This study uses qualitative method. The data are analyzed based on Jacobsonâ€™s theory. The result of this study shows that only 5 of 17 emotive language functions are applied. The emotive language functions applied are pleasure, like, dislike, surprise, gratitude. While the emotive language functions that not applied are hope, satisfaction, dissatisfaction, worry, preference, sympathy, intentions, want, desire, dear and disappointment. This study finds that the most emotive function that frequently used in the Ellen DeGeneres Talk Show is â€œlike expressionâ€. The emotive function in the Ellen DeGeneres talk show works to express the actorâ€™s feelings to other people based on the context and situation of the conversation